Tygodnik Katowicki . no. 13, 1981 - NSZZ "Solidarność" Regionu Śląsko-Dąbrowskiego, [Wiesław J. Asman EIC] (NSZZ "Solidarność" Region Śląsko-Dąbrowski, 1981)
Creation and circulation: For trade-union use